PENGARUH PROSEDUR OPERASI SC ELEKTIF DAN SC CITO TERHADAP KEJADIAN INFEKSI LUKA OPERASI DI RSUD BALANGAN - Febrianawati, Nita; Rahmawati , Dwi; Ulfa, Ika Mardiatul (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
One indicator of patient safety related to medical treatment is surgical wound infection which can be caused by the SC method of delivery.The incidence of SC in Balangan Regency is in 9th place out of 13 districts. From early January to November 2022, the incidence of CS at Balangan Hospital reached 315 out of 487 deliveries, with an incidence of post-SC wound infections of 33 or 10.47%. Research objective is to know the effect of elective SC and cito SC surgery procedures on the incidence of surgical wound infections in Balangan Hospital. This research method uses a case control study with a retrospective approach. The sample in this study were 35 post SC mothers. Analysis of the data used is the fisher's exact test. The results are there were 24 respondents (68.6%) doing Elective SC and 11 respondents (31.4%) doing CITO SC. The ILO incident was 4 respondents out of 35 SC respondents. The results of the Fisher's exact statistical test showed that the p-value was 0.082. Concluded that there is no relationship between the SC method and the incidence of ILO in post SC mothers and there may be other factors that influence it so that it is hoped that other researchers can explore more factors that can influence ILO in post SC.